Bricks and Roof Crafting: Spatial Changes on Land and the Solution - Anna, Alif Noor (Universitas Muhammadiyah Surakarta, 1996)
As a natural resource land has a strategic position in various development progress mainly as an infrastructure and means of settlement. At present it seems that land demand is getting increase adjusts to population growth and development rate. In connection to this question land problem has a close linkage in clay mining to obtain raw material of brick and tile. Clay as a manufactured raw material is usually extracted out from soil of agricultural field. Apparently, the clay mining has much changed physical and non physical condition, among others; lowering of land surface, reduction of soil fertility, micro relief changes, area constraction of groundwater charge supply, and there will be a decrease of flora and fauna variation at the operation area of the clay mining.